THE KILT AS A SYMBOL OF SCOTTISH IDENTITY - E. V. Voevoda (Концепт: философия, религия, культура, 2019)
The relevance of the research is determined by the growing interest to modern manifestations of Celtic culture, the desire of almost half of the population of Scotland to gain independence and the increasing attractiveness of Scotland as a tourist destination. As a result, the traditional symbols are viewed not only as trade and ethno-territorial brands, but also as social and ethnoculturally relevant imperatives. To achieve the objectives of defning the factors that inﬂuenced the transition of the kilt into an informal symbol of “Scottishness” it was imperative to consider the concept of Scottish identity and the role of the kilt in constructing its various forms: cultural, ethnic and national. The analysis of the existing approaches to studying identity and defnitions of the concept suggested by psychologists, philosophers, sociologists and experts in cultural studies allows to conclude that the kilt as one of the informal symbols of Scotland can be considered as a symbol of both cultural and national identity: the latter is explained by the fact that Scotland has such forms of statehood as autonomy, a coat of arms, a ﬂag, an anthem, its own parliament and languages – Scots (Anglo-Scottish) and Gaelic. The tradition of wearing the kilt by the representatives of the royal family, popularizing “Scottishness” by means of the tourist and entertainment industries makes it possible to speak about a new phenomenon – the perception of the kilt as the symbol of both Scottish and British culture.